PERBANDINGAN PRESTASI BELAJAR PADA MATERI METAMORFOSIS MENGGUNAKAN MODEL PICTURE AND PICTURE BERBANTUAN MEDIA PUZZLE DI KELAS IV - Maryemah, Maryemah; Hasmy, Ali; Setyaningrum, Saumi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The purpose of this study is to describe: first, the learning achievement of students in metamorphosis material in Class IV Ulumuddin private elementary school who is not taught using the picture and picture model with the help of puzzle media for the 2021/2022 school year. Second, the learning achievement of students in metamorphosis material in grade IV Ulumuddin private elementary school who is taught using a picture and picture model with the help of puzzle media for the 2021/2022 school year. Third, the difference in learning achievement of students who are taught using a picture and picture model with the help of puzzle media on metamorphosis material in Class IV Ulumuddin private elementary school in the 2021/2022 school year. This study uses a quantitative approach with an experimental method in the form of a quasi-experiment. The research location is Ulumuddin private elementary school, Jalan Parit Leban, Punggur Kecil Village, Sungai Kakap District. The data sources are fourth grade students. The technique is in the form of measurement, documentation. The tools are in the form of a test/question sheet and a camera. Data analysis used instrument analysis, descriptive analysis and inferential analysis. The results of this study were concluded, namely: First, the learning achievement of students on metamorphosis material in grade IV Ulumuddin private elementary school who did not use the picture and picture model with the help of puzzle media for the 2021/2022 academic year obtained a learning achievement value with a percentage of 56.16%. Second, the learning achievement of students on metamorphosis material in grade IV Ulumuddin private elementary school who uses a picture and picture model with the help of puzzle media, obtained a learning achievement value with a percentage of (86.03%) in the category of Very High learning achievement. Third, the difference in learning achievement between students who are taught using the picture and picture model with the help of puzzle media and those who do not use the picture and picture model with the help of puzzle media can be shown with a significance level value of 0.000 which is smaller than 0.005 and it can be seen the magnitude of the effect of using the model. picture and picture with puzzle media, there is a learning achievement of 0.863% × 100% = 86.3%.